Spectral Filtering For Removing Coal Bright Spot Effect In Seismic Interpretation - Saputro R.A; Suprajitno Munadi; Humbang Purba (Scientific Contributions Oil and Gas, 2012)
Gas Sand And Coal Bed Both Give Bright Appearence In Seismic Section. For The Purpose Of Gas Exploration One Has To Differentiate Between Gas Response And Coal Respone. A Spectral Fi Ltering Technique Is Introduced In This Paper To Solve This Problem. This Technique Is The Development Of The Spectral Decomposition Method Which Constitutes The Leading Edge In Seismic Data Analysis. Â Testing Using The Real Seismic Data Has Been Carried Out Using The Seimic Data From West Natuna Basin